Inactivation of Foodborne Pathogens and Their Surrogates on Fresh and Frozen Strawberries Using Gaseous Ozone - Zhou, Zijin; Zuber, Sophie; Cantergiani, Frédérique; Sampers, Imca; Devlieghere, Frank; Uyttendaele, Mieke (Frontiers in Sustainable Food Systems, 2018)
Berries represent an important fresh food commodity but are also used as dried or frozen ingredients added to many foods. Due to a number of foodborne outbreaks linked to frozen berries, the microbial safety of berry products has become a major food safety issue. The effect of gaseous ozone against selected strains was investigated in the present study at a laboratory scale. Among all the tested conditions, a 30 min treatment with 6% wt/wt (ca. 80 g/m3) gaseous ozone delivered the highest reductions on fresh strawberries: 2.1, 1.5, 1.8, and 3.3-log reductions were achieved for Salmonella, E. faecium, MNV-1 and MS2, respectively. For frozen strawberries, a short exposure of 5 min to ozone gas resulted in 1.6, 0.7, 0.7, and 1.8-log reductions of Salmonella, E. faecium, MNV-1 and MS2, respectively. Salmonella appeared to be more sensitive than its surrogate E. faecium. Compared to MS2, MNV-1 was more resistant and thus may represent as a more suitable surrogate for human norovirus in validating gas treatment efficiency. No sensorial differences were detected after ozone treatment. Inactivation results using gaseous ozone on frozen berries was reported for the first time in the present study. Guidelines on reporting gaseous ozone data were proposed to help ensure the reproducibility and experimental transparency in inactivation studies. Data collected in the present study support the potential use of gaseous ozone as a sustainable decontamination technology for frozen strawberries at different stages of processing. Further optimization of ozone exposure in a pilot plant scale setting is needed to facilitate the future application of gaseous ozone during minimal processing of berries.